Genetic components affecting embryonic developmental time of Drosophila melanogaster - Nascimento, Jurema Cruz do (2010)
The developmental time of the embryonic stage of Drosophila melanogaster was 21.66% faster and 14.75% slower than controls in populations selected for fast and slow developmental speed, respectively. The genetic model with two main loci with dominant and additive effect added to maternal effect and their relevant interactions can explain 96% of the phenotypic variability in the embryonic developmental time according to 14 crossing progenies involving fast and slow flies.